Representation of Communication Patterns Adults to Autism Children in Film Innocent Witness - Fabianus Valentino Setiawan; Fanny Lesmana (Journal of Content and Engagement, 2023)
Communication patterns help a person to communicate effectively with other people who have difficulty communicating. Difficulty in communicating is the main problem for autism children so that adults are needed to help them. It takes the right pattern of communication to understand the information that autism children want to convey. This depiction can be found in the film Innocent Witness which features a lawyer who mush know and be friends with autism child to help him solve the cases he is handling. This research was conducted with the aim of knowing how to describe the communication patterns of adults to autism children in this Innocent Witness film. The researcher will use a descriptive qualitative approach using John Fiske’s television semiotics method. From this study it was found that the communication patterns of adults to autism children experienced a process of finding the right communication patterns, namely adults having difficulty communicating with autism children before getting to know them, adults must understand autism children in the process of getting to know autism children, adults are able to create good communication effective with autism children after getting know autism children. And the idology of egalitarianism which adheres to equality for all people, including in communicatig with autism children.